The Quest for the Best Dual Orexin Receptor Antagonist (Daridorexant) for the Treatment of Insomnia Disorders. (28th October 2020) - Boss, Christoph; Gatfield, John; Brotschi, Christine; Heidmann, Bibia; Sifferlen, Thierry; von Raumer, Markus; Schmidt, Gunther; Williams, Jodi T.; Treiber, Alexander; Roch, Catherine
Abstract: Since its discovery in 1998, the orexin system has been of interest to the research community as a potential therapeutic target for the treatment of sleep/wake disorders, stress and anxiety disorders, addiction or eating disorders. It consists of two G protein‐coupled receptors, the orexin 1 and orexin 2 receptors, and two neuropeptides with agonistic effects, the orexin A and orexin B peptides. Herein we describe our efforts leading to the identification of a promising set of dual orexin receptor antagonists (DORAs) which subsequently went through physiology‐based pharmacokinetic and pharmacodynamic modelling> [1] and finally led to the selection of daridorexant, currently in phase 3 clinical trials for the treatment of insomnia disorders. Abstract : Since its discovery in 1998, the orexin system has been of interest to the research community as a potential therapeutic target for the treatment of sleep/wake disorders. Herein we describe our efforts leading to the identification of daridorexant, which successfully finished two pivotal phase 3 clinical trials for the treatment of insomnia disorders.